2019
DOI: 10.1089/vim.2019.0086
|View full text |Cite
|
Sign up to set email alerts
|

Subclinical Epstein-Barr Virus Primary Infection and Lytic Reactivation Induce Thyrotropin Receptor Autoantibodies

Abstract: Epstein-Barr virus (EBV) is a herpes virus that mainly infects in B lymphocytes and occasionally reactivates lytically. Most individuals have been infected with EBV primarily in their childhood with no symptoms, and the virus persists latently for life. We have previously reported that EBV-infected B cells with thyrotropin receptor autoantibodies (TRAbs) on their surface [TRAb(+) EBV(+) cells] were present in the peripheral blood mononuclear cells (PBMCs) of healthy adult controls and patients with Graves' dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 16 publications
2
6
0
Order By: Relevance
“…We also noted some reports that had detected autoantibodies released from lymphocytes infected with exogenously-added EBV [18][19][20][21]. Tamoto et al recently reported that serum thyrotropin receptor antibodies (TRAbs) may be present even in asymptomatic EBV primary infection [22]. These findings support a relationship between EBV infection and autoimmunity.…”
Section: Introductionsupporting
confidence: 82%
“…We also noted some reports that had detected autoantibodies released from lymphocytes infected with exogenously-added EBV [18][19][20][21]. Tamoto et al recently reported that serum thyrotropin receptor antibodies (TRAbs) may be present even in asymptomatic EBV primary infection [22]. These findings support a relationship between EBV infection and autoimmunity.…”
Section: Introductionsupporting
confidence: 82%
“…More recently, rs7197 SNP has been found to be closely related to the antibody response to viral elements such as capsid antigen of Epstein-Barr virus, and it is speculated that rs7197 genetic variation may play a role in disease susceptibility through immune-mediated specific microbial genes [31]. Combining our study with previous in vitro and in vivo evidence that Epstein-Barr virus infection is associated with TRAb production and GD occurrence [38,39], it is reasonable to infer that there is a natural association between rs3177928, rs7197 polymorphisms, and AITD development.…”
Section: Discussionsupporting
confidence: 71%
“…Moreover, during the primary infection, TRAb(+) cells, EBV(+) cells, and TRAb(+) EBV(+) cells were small, but they expanded during EBV lytic reactivation. EBV infection reactivation might be associated with B lymphocytes expansion, and GD recurrence in Japanese patients (64).…”
Section: Epstein-barr Virusmentioning
confidence: 99%
“…In primary EBV infection, some infected cells become lytic. During infectious mononucleosis (IM), in the acute phases, defined as the symptomatic EBV primary infection, different autoantibodies are present in the serum of patients (64). EBV primary infection and lytic infection induce the production of antibodies.…”
Section: Epstein-barr Virusmentioning
confidence: 99%